Analysis of the Electrical Characteristics of an Alternative Solution for the Brazilian-Amazon Transmission System - Pinto, Andre J. G.; Costa, Eduardo C. M.; Kurokawa, Sergio [UNESP]; Pissolato, Jose (Taylor & Francis Inc, 2011)
This article analyzes the electrical parameters of a 3-phase transmission line using a 280-m-high steel tower that has been proposed for the Amazon transmission system in Brazil. The height of the line conductors and the distance between them are intrinsically related to the longitudinal and transverse parameters of the line. Hence, an accurate study is carried out in order to show the electrical variations between a transmission line using the new technology and a conventional 3-phase 440-kV line, considering a wide range of frequencies and variable soil resistivity. First, a brief review of the fundamental theory of line parameters is presented. In addition, by using a digital line model, simulations are carried out in the time domain to analyze possible and critical over-voltage transients on the proposed line representation.
Keywords: transmission line; electric parameters; steel tower; Amazon energy transmission